Soil Moisture Monitoring System and Soil PH on IoT-based Aglaonema Crop - Rosliana Eso; La Ode Safiuddin; Asih Nofriasih Kalam (PTE FTK UIN Ar-Raniry, 2023)
Aglaonema is an ornamental plant with soft, watery (herbaceous) stems that dislikes too moist media and needs precise irrigation. Using Internet of Things (IoT) technology, which integrates soil moisture sensors YL-69 Soil moisture sensor, soil pH sensors, and NodeMCU ESP8266 as a microcontroller with the Thingspeak IoT Platform and the Blynk Application via Android, it is possible to monitor soil moisture and pH, which is a determining factor in the planting media for ornamental plant cultivation. Additionally, it may enable remote control operation of a watering system for ornamental plants that holds soil moisture when it exceeds a predetermined threshold. The design of an IoT (Internet of Things)-based soil moisture and pH monitoring system has successfully been applied to the cultivation of ornamental plants. This is expected to help owners of cosmetic plant businesses make decisions based on online information about soil moisture and pH values.